تعليم الإملاء في معهد تربية المعلمين الإسلامية "الأمين" برندوان سومنب مادورا - Latifatul Mahbubah; Asmaul Husna (Lugawiyyat, 2021)
Writing is like reading a communication activity that belongs to written skills, and writing in Arabic learning was one of the linguistic skills, in general, the goals of its teaching are the students' ability to communicate in writing in the Arabic language.  Dictation is an essential writing skill so that students can express their minds in good and correct writing. This research aims to know the steps of teaching of dictation at the TMI Al-Amien Prenduan Boarding School and how to correct it. In this research, the researcher used the descriptive approach with the qualitative approach to learn the steps of teaching of dictation at the TMI Al-Amien Prenduan Boarding School and how to correct it through observation, interview and documentation. The results of the research from this research are as follows: imla' learning material taken from some muthala'ah material. The teaching of dictation used is listening dictation and the method of correcting it is the reciprocal method, which is the exchange of students' notebooks with its neighboring friend, then the teacher ordered some students to write the specified sentence on the blackboard along with the teacher checks the written text on the blackboard.